MANAJEMEN KERJASAMA PONDOK PESANTREN ALAM INTERNASIONAL SAUNG BALONG AL-BAROKAH DENGAN MASYARAKAT DALAM PENGEMBANGAN EKONOMI DAN PENDIDIKAN - Kurniawan, Asep (Pascasarjana IAIN Kudus, 2014)
Abstract : Pesantren should not only concentrate on developingreligious education only, but also must be concerned on localeconomy. This concern is a manifestation of partnership managementbetween pesantren and community. In fact, many Pesantrens are notable to play such a role in an integrated way. This study aimed to findpartnership management patterns in Pesantren Alam InternasionalSaung Balong al-Barokah and the community in the context ofmanagement education in economic and education. The researchmethod was qualitative. Instruments of collecting data were aninterview, unstructured observation, and documentation. Datavalidation was done through credibility, transferability, dependabilityand conformability. Techniques of data analysis were done bycollecting the data, reducing data, displaying data, and concludingdata. Researcher found that Pesantren Alam Internasional SaungBalong al-Barokah successfully worked together in harmony with thecommunity in economic empowerment and education in an integratedway, so could provide the benefits. These findings should be emulatedby other pesantren.